Osseointegration at implants placed into delayed reimplanted roots: An experimental study in dogs - Cardoso, Leandro de Carvalho; Poi, Wilson Roberto [UNESP]; Botticelli, Daniele; Garcia Júnior, Idelmo Rangel [UNESP]; Pantani, Fabio [UNESP]; Silva Pereira, Cassiano Costa [UNESP] (Wiley-Blackwell, 2014)
AimTo evaluate peri-implant bone repair of implants placed into the roots of delayed reimplanted teeth, in a process of ankylosis and external replacement resorption.Material and methodsThe third and fourth mandibular premolars of four (4) beagle dogs were used as experimental sites. The study was divided into three stages: stage 1 - endodontic and extraction/reimplantation session, stage 2 - decrowning session and stage 3 - implant placement. Two groups were identified: (I) immediate implants, including implants installed in fresh extraction sockets of the distal roots, and (II) experimental implants, including implants installed into the retained ankylotic mesial roots. In each group, 16 implants were planned to be inserted, but only 9 immediate implants and 12 experimental implants were used for analyses. Implants were intended to heal in a submerged mode. After 4 months of healing, the animals were sacrificed and ground sections were obtained for histomorphometric evaluation.ResultsEleven of the twelve implants in the experimental group were found successful regarding clinical and radiographic aspects. For immediate implants, a lower BIC% was found at the coronal portion (BIC% 1=42.2%) compared with the three most coronal threads portion (BIC% 2=55.1). Also, experimental implants presented a lower BIC% at the coronal portion (BIC% 1=36.9%) compared with the three most coronal threads portion (BIC% 2=45.3).ConclusionComparison between groups showed a higher degree of BIC% and mineralization in immediate group compared with experimental group. The differences, however, did not yield statistical significance.
Keywords: animal study; tooth extraction; implant dentistry; reimplantation; bone healing; immediate implant; osseointegration; dental ankylosis